2020
DOI: 10.3390/w12041195
|View full text |Cite
|
Sign up to set email alerts
|

Rainfall Threshold Estimation and Landslide Forecasting for Kalimpong, India Using SIGMA Model

Abstract: Rainfall-induced landslides are among the most devastating natural disasters in hilly terrains and the reduction of the related risk has become paramount for public authorities. Between the several possible approaches, one of the most used is the development of early warning systems, so as the population can be rapidly warned, and the loss related to landslide can be reduced. Early warning systems which can forecast such disasters must hence be developed for zones which are susceptible to landslides, and have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…The study clearly points out to the significance of considering both long-term and short-term rainfall for developing rainfall thresholds for the region. This accounts for the higher number of false alarms reported for the conventional empirical thresholds defined for the study area [8,49]. In 2018, the rainfall received was the lowest when compared to the 2017 and 2019 monsoons.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The study clearly points out to the significance of considering both long-term and short-term rainfall for developing rainfall thresholds for the region. This accounts for the higher number of false alarms reported for the conventional empirical thresholds defined for the study area [8,49]. In 2018, the rainfall received was the lowest when compared to the 2017 and 2019 monsoons.…”
Section: Discussionmentioning
confidence: 94%
“…From the summary, it is clear that antecedent rainfall plays a major role in ground displacement rather than daily rainfall values. Hence, the study points out the significance of using a statistical threshold that considers the effect of both short-term and long-term rainfall as the first line of early warning [49]. Such thresholds can also be conceptually modified by incorporating moisture content [8,14,50] and tilt angle values.…”
Section: Monsoon 2019mentioning
confidence: 99%
“…In India, the Himalayan belt [4,[22][23][24] and the Western Ghats [25,26] are highly prone to landslides.…”
Section: Introductionmentioning
confidence: 99%
“…Segoni et al (2018b) pointed out that before the implementation into operational EWS, rainfall thresholds should be carefully validated and evaluated, but this good practice is not fully consolidated. Indeed, some studies conclude that a complete validation shows that the main drawback of the EWS at hand is that a good hit rate is usually achieved at the cost of a high number of false positives (false alarms) (Rosi et al, 2016(Rosi et al, , 2019Abraham et al, 2020;Gariano et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…However, antecedent rainfall and rainfall intensity have been usually considered mutually exclusive, and one of the two approaches is usually selected depending of the characteristics of the test site and the typology of the studied landslides. Other researchers developed complex decisional algorithms based on long-term rainfall anomalies (Martelloni et al, 2012) and observed that in some particular settings (e.g., Emilia Romagna, Italy, and Indian Himalaya) they could outperform simpler approaches based on rainfall intensity, rainfall duration, or event rainfall (Lagomarsino et al, 2015;Abraham et al, 2020). Another series of works, starting from the rationale that landslides are triggered by the increase of water pore pressure and not by rainfall itself, tried to include soil moisture conditions in the threshold modeling (Terlien, 1998;Ponziani et al, 2012;Valenzuela et al, 2018;Wicki et al, 2020).…”
Section: Introductionmentioning
confidence: 99%